Permainan Dadu pada Pengembangan Perilaku Prososial Anak di RA An-Nur Kota Kendari - La Hewi; Surpida Surpida (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2019)
The game can not be separated from learning in early childhood. Games that involve several children will establish social relationships between one child and another child. PAUD unit educators pay less attention to stimulation in the development of prosocial behavior of children but most educators focus on providing stimulation for cognitive aspects, language and religious and moral values ??as an important aspect of development to be stimulated. The dice game is used to stimulate the development of prosocial behavior of early childhood group A RA An-Nur, Kendari City. The research method used is action research. The model chosen for action is the Kemmis and Taggart cycle which has four stages of planning, action, observation and reflection. Data on the development of a child's prosocial behavior were obtained through observation and subsequent documentation analyzed using a percentage. The study was conducted in two cycles, each cycle having three meetings. The results showed that dice games can improve the development of prosocial behavior in early childhood.